TWO SCALES OF INFLATION AT LASTARRIA-CORDON DEL AZUFRE VOLCANIC COMPLEX, CENTRAL ANDES, REVEALED FROM ASAR-ENVISAT INTERFEROMETRIC DATA - Froger J.L.; Remy D.; Bonvalot S.; Legrand D. (My University, 2007)
ASAR-ENVISAT Interferometric Synthetic Aperture Radar (InSAR) data collected over the Lastarria-Cordon del Azufre complex (Chile-Argentina) between March 2003 and May 2005 show the persistence of the large wavelength ground inflation revealed by Pritchard and Simons in 2002 from the analysis of ERS InSAR data [Nature 418 (2002) 167-170]. After reducing the tropospheric contribution in the interferograms using a combination of data network adjustment and analysis of MODIS images, we produced an accurate interferometric time series showing a 2 yr long temporal evolution of the ground displacements patterns. Two distinct inflating signals are detected. The main signal covers an elliptical area with a 45 km NNE-SSW major axis and a 37 km minor axis. It is correlated with a regional topographic dome. We estimated its maximum inflation rate to ~ 2.5 cm yr- 1. We inverted the InSAR data for a range of source geometries (spherical, prolate ellipsoids, penny-shaped cracks). The inferred source parameters for 2003-2005 period are consistent with an over-pressured reservoir at shallow to intermediate crustal depths (7-15 km), with an average volumetric rate of inflation of about 14 × 106 m3 yr- 1. In addition to this main signal a new feature highlighted by the ASAR data is short wavelength inflation (6 km wide) at the location of Lastarria volcano on the northern margin of the large wavelength signal. We explain this short wavelength signal by a spherical over-pressured source lying 1000 m below the summit of Lastarria volcano. We estimate the average volumetric rate of inflation during the observation period to be ~ 35 × 103 m3 yr- 1. It is remarkable that both volumetric variations for the large and small inflations exhibit the same evolution during the 2003-2005 period, suggesting that both processes could be related. On the basis of the inversion results and of arguments provided by field evidences and a morpho-structural analysis of the Digital Elevation Model of the area, we propose that the deep source have a magmatic origin while the shallow source is most likely related to hydrothermal fluids. In our interpretation, the on-going deformation processes observed at Lastarria-Cordon del Azufre volcanic complex could represent an evolving pre-caldera silicic system. Further field geological and geophysical investigations will be required to confirm these hypotheses and refine the proposed model, mostly based on satellite observations. © 2007 Elsevier B.V. All rights reserved.
Keywords: ANDES; DISPLACEMENTS; INTERFEROMETRY; LASTARRIA; LAZUFRE; VOLCANOES